The legend of Korra : turf wars. Part two - DiMartino, Michael Dante (Dark Horse Books, 2018)
Returning to the Spirit World, Korra and the Airbenders discover that it has become a barren landscape, meanwhile on the outskirts of the portal General Iroh's choice to establish a military presence threatens the balance of human and spirit relations.